Cardiac disease in pregnancy - Thakkar, Nidhi D.; Agarwal, Sonali N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Cardiac disease is an important cause of maternal morbidity and mortality. It can invariably affect fetus with variable intensity depending upon nature of cardiac disease in mother. Cardiac disease can affect women antenatally, in labor and even in post-partum period. It is a case series of 12 cases who presented to labor room in a particular unit at SSG hospital, Baroda over a period of 1 year starting from 1st May 2022 to 30th April 2023. Mean age at presentation was 24.8. 3 women were having valvular heart disease while 4 were having peri-partum cardiomyopathy (PPCM), 4 were having atrial septal defect (ASD), 1 was having ventricular septal defect (VSD). Associated medical comorbidities and obstetrical factors were evaluated. 2D ECHO findings of all cases were recorded. Risk assessment must be done for the mother and fetus to minimize the effect of cardiac disease in pregnancy. Joint consultation with cardiologist should be done in already known case of cardiac disease.